The influence of fishing tools using different feed towards variation of Loligo sp. catches in the Takalar Sea of South Sulawesi, Indonesia - Daris, Lukman; Massiseng, Andi Nur Apung; Jaya, Jaya; Irsandi, Irsandi (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Fishery is one of the human activities to utilize aquatic resources in fresh, brackish and marine waters. This effort is made to meet the needs of human life for the availability of animal protein for growth and as a source of meeting other economic needs. Fishery business consists of components that are interrelated with one another, namely capture fisheries and aquaculture and supported by marketing and processing of fishery products. One of the fishing gear used by fishermen around the coast is a hand line. The purpose of this study was to find out which light are effective in the operation of hand line fishing gear in Takalar waters. The data collection technique was done by using the trial method (Expermental fishing), by conduction trials using two different lamps, namely LED lights (light emitting diode) and petromax lamps. This research was conducted in Takalar Waters in July-August 2020. The results showed that the size structure of the squid and cuttlefish caught on the LED lights ranged from 6- 27.5 cm, totaling 310 tail, weighing 41.15 kg (69.51%), whilw the size structure of the squid caught in the petromax lamp ranges 9,5-27,6 cm totaling 136 tail, weighing 17.91 kg (30.49%), significantly different from the result of t-student.